Hakekat Manusia Menurut Muhammad Iqbal dan Kahlil Gibran - Dini Kusumandari Lubis (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
Human nature, is an expression that is very interested in being discussed by philosophers including Iqbal and Gibran. Their interest in human studies can be found in their various works. According to Iqbal, humans are the most noble creatures, while Gibran argues that humans are social beings as well as individual beings, therefore he is aware of himself and then loves himself. The purpose of this study was to determine the thoughts of Iqbal and Gibran about Human Nature. The results of research on the Human Nature of Muhammad Iqbal and Kahlil Gibran's thoughts, namely Iqbal made the main idea for the nature of Muslim humans. He re-adapted the Persian idea of khudi by removing its negative meanings: selfishness and selfishness. Then he put the idea of khudi in a positive form. According to Gibran, human nature is "love". Humans are creatures of love, love is the greatest gift of God that he gave to humans. As the culmination of that love is to love the creator.